1 SAM 15: 1-35 dan PERANG SUCI - Stanislaus, Surip (UNIKA Santo Thomas, 2008)
A holy war is a war held in the contect of faith in God. In this kind of war, the role of God is so dominant, so that this war is believed God himself who is wagging the war. The war is called a holy war because God is holy. A holy war is not just a war for the sake of war, but for the sake of a fidelity to the will and God’s rule. To keep this war holy and so would grant a victory, the troop shoul obey the ritual rule of war. 1 Sam 15: 1-35 is an example of Saul’s infidelity to the rule of war which causes God’s anger.